Termos semelhantes
![a3 - 1y + 5a - 2y a3 - 1y + 5a - 2y](https://tex.z-dn.net/?f=+a3+-+1y+%2B+5a+-+2y)
Soluções para a tarefa
Respondido por
3
Olá!!!
Resolução!!!
= a3 - 1y + 5a - 2y
= a3 + 5a - 2y - 1y
= 8a - 3y
R = 8a - 3y
Espero ter ajudado!!
Resolução!!!
= a3 - 1y + 5a - 2y
= a3 + 5a - 2y - 1y
= 8a - 3y
R = 8a - 3y
Espero ter ajudado!!
Perguntas interessantes
Matemática,
11 meses atrás
Biologia,
11 meses atrás
Biologia,
11 meses atrás
Geografia,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás